2014
DOI: 10.1038/cddis.2014.384
|View full text |Cite
|
Sign up to set email alerts
|

A sphingosine kinase inhibitor combined with temozolomide induces glioblastoma cell death through accumulation of dihydrosphingosine and dihydroceramide, endoplasmic reticulum stress and autophagy

Abstract: Glioblastomas (GBMs) are very aggressive tumors with low chemosensitivity. The DNA-alkylating agent temozolomide (TMZ) is currently the most efficient chemotoxic drug for GBM therapy; however, many patients develop resistance to TMZ. Combining TMZ with another agent could present an improved treatment option if it could overcome TMZ resistance and avoid side effects. Sphingosine kinase inhibitors (SKIs) have emerged as anticancer agents. Sphingosine kinases are often overexpressed in tumors where their activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 41 publications
8
51
0
1
Order By: Relevance
“…Indeed, SKIs, other inhibitors of Cer metabolism and Cer itself all synergistically enhance the apoptotic efficacy of MTAs. 3949 More recently, it has been suggested that Cer may actually be required for paclitaxel induced mitochondrial outer membrane permeabilization (MOMP) and apoptosis. 50 Mechanistically, sphingolipids have also been shown to activate the pro-apoptotic Bcl-2 family proteins Bak and Bax.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, SKIs, other inhibitors of Cer metabolism and Cer itself all synergistically enhance the apoptotic efficacy of MTAs. 3949 More recently, it has been suggested that Cer may actually be required for paclitaxel induced mitochondrial outer membrane permeabilization (MOMP) and apoptosis. 50 Mechanistically, sphingolipids have also been shown to activate the pro-apoptotic Bcl-2 family proteins Bak and Bax.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, there are numerous examples in the literature of SKIs interacting synergistically with both targeted and cytotoxic chemotherapies. 39,6870 A highly selective non-cytotoxic SphK inhibitor, such as PF-543, may be an ideal adjuvant to current chemotherapeutic regimens. In such an instance, inhibition of S1P production and/or accumulation of Cer could enhance induction of apoptosis of the standard-of-care regimens.…”
Section: Discussionmentioning
confidence: 99%
“…We compared the effects of applying a sphingosine kinase inhibitor (SKI), known to impair survival and invasion of the glioma cells18, on spheroids generated after 72 h (87 spheroids of 90) and 144 h (78 spheroids of 90) (Fig. 6).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, SKI-II has been shown to decrease cellular S1P, increase cellular ceramides and sphingosine, and induce apoptosis [66,68]. Furthermore, it has been demonstrated to enhance the effects of other anti-cancer agents on cell lines, including sensitising a panel of glioblastoma lines to temozolomide [69], chemo-resistant MCF7-TN-R breast cancer cells to doxorubicin [70], and head and neck squamous cell carcinoma cell lines to the EGF receptor inhibitor, Cetuximab [71].…”
Section: Ski-iimentioning
confidence: 97%